Improving irrigated agriculture through integrated water resources management in Pusur Watershed, Central Java. Issue 1 (February 2021) - Hamdani, A; Kartiwa, B; Sosiawan, H
Abstract: Pusur watershed supplies water for about 3, 000 ha irrigated farmlands of 12, 000 smallholders. However, water shortages affecting the crop development and production are common in the farmlands within the Pusur Watershed, especially during the 3 rd cropping season (June-October). This research conducted a survey to describe water resources availability, hydraulic network performance, cropping calendar, canal water access, and crop development condition with objectives to improve water management and reduce water conflict in the irrigated region. The participatory and rapid appraisal results identified different condition of canal water access and crop development within the sampling area. The result found that the pusur watershed is very elongated shape and the largest area was covered by 44.24 % of rice. Water availability of all dams in Pusur Watershed are decreasing from rainy season to dry season about 8 until 19% in every year. Many farmers has a good access in hydroulic structure condition and water distribution efficiency, but most of them has canal water lack for crop during the 3 rd cropping. An analysis of water balance simulation showed a degraded conditions of crop development most located in downstream areas whereas crops look growing-up normally in most of upstream zones.